2007
DOI: 10.1017/s0020818307070026
|View full text |Cite
|
Sign up to set email alerts
|

Argumentation and Compromise: Ireland's Selection of the Territorial Status Quo Norm

Abstract: How do states come to select norms? I contend that, given a number of conditions are present, states select norms in three ideal-typical stages: innovative argumentation, persuasive argumentation, and compromise+ This norm selection mechanism departs from the existing literature in two important ways+ First, my research elaborates on the literature on advocacy networks+ I explain why agents engage in an advocacy for a normative idea in the first place; I add the epistemic dimension of reasoning to argumentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…McCall (1998McCall ( , 1999McCall ( , 2001 has clearly demonstrated that there has been a realignment of nationalist territorial identity but has chosen to focus on the SDLP (a leading Northern Irish Party) and has excluded southern constitutional nationalism (in particular the leading Fianna Fáil Party in the Irish Republic) from his remit. By limiting their study to the official nationalist discourse in the Republic of Ireland (Kornprobst 2007;Hayward 2006Hayward , 2009), others also minimize or even ignore the tensions and divergences between Irish constitutional nationalist parties, especially the SDLP (northern party) and Fianna Fáil (southern party).…”
Section: Some Implications Of Insisting Upon the Importance Of Reterrmentioning
confidence: 99%
See 2 more Smart Citations
“…McCall (1998McCall ( , 1999McCall ( , 2001 has clearly demonstrated that there has been a realignment of nationalist territorial identity but has chosen to focus on the SDLP (a leading Northern Irish Party) and has excluded southern constitutional nationalism (in particular the leading Fianna Fáil Party in the Irish Republic) from his remit. By limiting their study to the official nationalist discourse in the Republic of Ireland (Kornprobst 2007;Hayward 2006Hayward , 2009), others also minimize or even ignore the tensions and divergences between Irish constitutional nationalist parties, especially the SDLP (northern party) and Fianna Fáil (southern party).…”
Section: Some Implications Of Insisting Upon the Importance Of Reterrmentioning
confidence: 99%
“…The European institutions are not the only supra-state institutions that have led Irish nationalism to reshape its territorial discourse. Others such as the United Nations or the Conference on Security and Cooperation in Europe (CSCE), for instance, have also been influential in bringing about a redefinition of the nationalist conception of selfdetermination and its endorsement of the norm of the territorial integrity of states (Kornprobst 2007). …”
Section: Some Implications Of Insisting Upon the Importance Of Reterrmentioning
confidence: 99%
See 1 more Smart Citation
“…4. This conception of the domestic social structure is informed by the work of Bernstein (2001: 186), Kornprobst (2007) and Risse-Kappen (1994: 187, 208Á9). 5.…”
Section: Constructivist Scholars Of International Relations Have Propmentioning
confidence: 99%
“…Secondly, the actual shape of the rules is somewhat moot. It is enough to make the point that argumentation is a social practice that one observes the Wittgensteinian principle 7 This point is also made--and illustrated byconcrete political examples--in Kornprobst (2007).…”
mentioning
confidence: 98%